2013
DOI: 10.1038/srep01809
|View full text |Cite
|
Sign up to set email alerts
|

Prominent role for T cell-derived Tumour Necrosis Factor for sustained control of Mycobacterium tuberculosis infection

Abstract: Tumour Necrosis Factor (TNF) is critical for host control of M. tuberculosis, but the relative contribution of TNF from innate and adaptive immune responses during tuberculosis infection is unclear. Myeloid versus T-cell-derived TNF function in tuberculosis was investigated using cell type-specific TNF deletion. Mice deficient for TNF expression in macrophages/neutrophils displayed early, transient susceptibility to M. tuberculosis but recruited activated, TNF-producing CD4+ and CD8+ T-cells and controlled chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 64 publications
7
103
3
2
Order By: Relevance
“…Taking this into account, a possible improvement of existing anti-TNF therapeutic options by selective inhibition of TNF produced by macrophages appears reasonable. A recent study demonstrated that for the resistance to Mycobacterium tuberculosis infection in mice T-cell-derived TNF appears critical and nonredundant for immune protection (41). This is consistent with the mode of protection through the formation of bactericidal granulomas whose structural integrity depends on TNF produced by T cells, presumably in membrane-bound form (41,42).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Taking this into account, a possible improvement of existing anti-TNF therapeutic options by selective inhibition of TNF produced by macrophages appears reasonable. A recent study demonstrated that for the resistance to Mycobacterium tuberculosis infection in mice T-cell-derived TNF appears critical and nonredundant for immune protection (41). This is consistent with the mode of protection through the formation of bactericidal granulomas whose structural integrity depends on TNF produced by T cells, presumably in membrane-bound form (41,42).…”
Section: Discussionsupporting
confidence: 53%
“…A recent study demonstrated that for the resistance to Mycobacterium tuberculosis infection in mice T-cell-derived TNF appears critical and nonredundant for immune protection (41). This is consistent with the mode of protection through the formation of bactericidal granulomas whose structural integrity depends on TNF produced by T cells, presumably in membrane-bound form (41,42). In both humans and mice, systemic anti-TNF treatment is known to affect granuloma integrity and may cause reactivation of latent disease (43).…”
Section: Discussionmentioning
confidence: 58%
“…We did not evaluate TNF, which would be another candidate because TNF −/− mice and humans treated with TNF antagonists are susceptible to mycobacterial infection. It has been shown that both Tcell and myeloid-cell TNF are required for mycobacterial control in mice (54). IL-22 deficiency did not impair the effect of transferred T cells in reducing bacterial transcripts in Rag −/− lymph nodes.…”
Section: Rag1-/-skin-lymph Nodesmentioning
confidence: 87%
“…Finally, TNF has a variety of immunoregulatory actions including promoting granuloma integrity. Elucidating how TNF contributes to anti-mycobacterial defense is complicated because multiple cell types produce it [141]. Allie et al investigated cell type specific TNF −/− mice and found that while myeloid cell expression of TNF is important for cell recruitment to the lung, initiation of T cell immunity and establishment of lung lesions appeared normal [141].…”
Section: 0 Mechanisms Of Protectionmentioning
confidence: 99%
“…Elucidating how TNF contributes to anti-mycobacterial defense is complicated because multiple cell types produce it [141]. Allie et al investigated cell type specific TNF −/− mice and found that while myeloid cell expression of TNF is important for cell recruitment to the lung, initiation of T cell immunity and establishment of lung lesions appeared normal [141]. In contrast, mice with a T cell-specific TNF −/− were unable to control the infection during the chronic phase of the infection and died prematurely.…”
Section: 0 Mechanisms Of Protectionmentioning
confidence: 99%